Estudo da pressão intracraniana em pacientes com fibrilação atrial por metodologia não invasiva - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia associated with high death rates, stroke, heart failure, ventricular dysfunction, and decreased quality of life. Arterial hypertension may be present in up to 70% of patients with AF. Patients with AF generally receive anticoagulant therapy to prevent the risk of stroke, but on the other hand may increase the risk of intracranial hemorrhage. Both ischemia and cerebral hemorrhage can lead to stroke and increase intracranial pressure (ICP). Intracranial hypertension has an effect on cerebral perfusion, which may also result in ischemia or secondary brain injury. The aim of this study was to evaluate ICP in two patient groups: atrial fibrillation (AF) and control group without atrial fibrillation (CON) using a noninvasive methodology. The methodology for the evaluation of PIC consisted of an external chip system that transmits, in real time, electrical signals of cranial deformation to a monitor. In this study, we observed that the FA group presented age (: 0.004), fasting glycemia, glycosylated hemoglobin (HbA1c), urea and creatinine higher than the control group. There was no difference regarding gender or BP. The number of people with altered ICP was 58.8% in the AF group and 46.7% in the CON group (: 0.7393); The AF group presented more intense alterations than the control group (: 0.013). The ICP was directly correlated with the SBP group, but not with the AP of the FA group. The noninvasive evaluation of ICP is an excellent tool, as it was able to discriminate the intensity of the P2 / P1 relationship between the two groups. However, further studies are needed to understand the significance of PIC change in patients with AF.
Keywords: Pressão intracraniana; Fibrilação atrial; Acidente vascular encefálico; Intracranial pressure; Atrial Fibrillation; Stroke; CNPQ::CIENCIAS DA SAUDE::FARMACIA